Reform of the international monetary system: some concrete steps - Agnès Bénassy-Quéré; Jean Pisani-Ferry; Yu Yongding (Bruegel, 2011)
Reform of the international monetary system is under discussion after three decades of apathy. Tectonic shifts in the balance of international power have made reform more urgent. However, in the short term, there is little chance of a grand redesign of the international monetary system. Nevertheless, concrete steps should be taken. First, consensus is needed on exchange rates, capital flows and reserves. Second, financial safety nets must be improved so that countries do not have to self-insure by accumulating reserves or rely on possible bilateral swap lines to access liquidity. Third, a change in the composition of the Special Drawing Right should be planned for, to strengthen the multilateral framework. The most workable short-term deliverables seem to be (i) guidelines on and surveillance of capital controls; (ii) a new regime for deciding on SDR allocations that would facilitate more frequent use of this instrument; and (iii) the inclusion of the renmimbi in the SDR basket. These reforms would be a partial move, preparing the ground for further developments.
Keywords: 330